Dual role of miR-155 and exosomal miR-155 in tumor angiogenesis: implications for cancer progression and therapy - Qusay Mohammed Hussain; Ali Fawzi Al-Hussainy; Gaurav Sanghvi; R. Roopashree; Aditya Kashyap; D. Alex Anand; Rajashree Panigrahi; Nargiz Shavazi; Sada Ghalib Taher; Mariem Alwan; Mahmood Jawad; Hiba Mushtaq (European Journal of Medical Research)
Abstract Tumor angiogenesis facilitates cancer progression by supporting tumor growth and metastasis. MicroRNA-155 (miR-155) plays a pivotal role in regulating angiogenesis through both direct effects on tumor and endothelial cells and indirect modulation via exosomal communication. This review highlights miR-155’s pro-angiogenic influence on endothelial cell behavior and tumor microenvironment remodeling. Additionally, exosomal miR-155 enhances intercellular communication, promoting vascularization in several cancers. Emerging therapeutic strategies include miR-155 inhibition using antagomirs, exosome-mediated delivery systems, and modulation of pathways such as JAK2/STAT3 and TGF-β/SMAD2. Targeting miR-155 represents a promising approach to hinder tumor angiogenesis and improve cancer therapy outcomes.